The Health Belief Model as an explanatory framework for COVID-19 prevention practices - Dania E. Alagili; Mohamed Bamashmous (Elsevier, 2021)
Background: The COVID-19 government public health measures are necessary to prevent the spread of COVID-19, however, their efficacy is largely dependent on adherence. This study utilized the Health Belief Model (HBM) to explain the public's adopted prevention practices during the COVID-19 outbreak in Saudi Arabia. Methods: This study used "COVID-19 Snapshot MOnitoring (COSMO): monitoring knowledge, risk perceptions, preventive behaviours, and public trust in the current coronavirus outbreak" research protocol which is developed by the WHO Regional Office for Europe and the COSMO group. The COSMO questionnaire was translated into Arabic and distributed as an online survey via WhatsApp instant messaging application from May 2nd to May 26th, 2020. The dependent variable was the mean of adopting ten COVID-19 preventive practices. These practices were hand washing, avoiding touching eyes, nose and mouth, use of hand sanitizer, covering mouth and nose when coughing/sneezing, staying home when sick, avoiding close contact with infected persons, social distancing, wearing masks, home isolation, and lockdown. The independent variables included the HBM constructs (susceptibility to and severity of COVID-19, benefits of and barriers to adopting preventive behaviors, cues to action, health motivation, and self-efficacy), sociodemographic factors, presence of chronic illness, and perceived and actual knowledge. We conducted bivariate and multivariate analyses and reported significant findings (P ≤ 0.05). Results: We analyzed 1027 surveys. About 38% adhered to all COVID-19 preventive behaviors and the mean for adherence was 9. The HBM perceived benefits (p = 0.001), perceived barriers (p = 0.004), and cues to action (p = 0.046) were associated with adherence to COVID-19 preventive behaviors after adjusting for all other factors. Respondents with the highest levels of education and income were less likely to adopt COVID-19 preventive behaviors compared to those in the lower ranks of education and income. Conclusion: Our findings suggest that the HBM can be applied to understand adherence to COVID-19 prevention practices. The recognition of perceived health beliefs and practices is important for developing effective COVID-19 health intervention strategies.